STUDENTSâ€™ ABILITY IN COMPREHENDING MOVIE ENTITLED â€œMY BIG FAT GREEK WEDDINGâ€ OF ENGLISH EDUCATION STUDENTS OF BATANGHARI UNIVERSITY: A CROSS-CULTURAL UNDERSTANDING - Nurul Fitri (Universitas Khairun, 2021)
The purpose of this research is to identify how far students of English Education program of Batanghari University can understand the differences of cultures that can be seen from the movie entitled â€œMy Big Fat Greek Weddingâ€. Their comprehension about the cross cultural understanding will be notified from their analysis towards the movie. The subject of this research is semester VI students of class A1 which consists of 23 students. Meanwhile the object of the research is studentsâ€™ analysis of cross cultural matters in a form of interview after they watch the movie. The method used in this research is mix method. Qualitative approach is used in analyzing the cross cultural matters in their analysis towards the movie and quantitative approach is used to count the forms of cross cultural matters that occured from the movie. The hypothesis of this research is that the students are able toÂ understand the difference of other cultures especially American, British, or Australian culture which is related to their major.